Environmental characterization on anuran assemblage in two habitat types of Terla Forest Reserve - Simon, Nadia (2020)
Forest conversion to agricultural farmland modifies land into small patches, making amphibians more dependable to external environmental changes. Besides, monitoring studies of the restoration process in birds and mammals are greater compared to anuran studies. A study on anuran between two habitat types was conducted in Cameron Highlands from June 2018 until February 2019 to investigate the species diversity, richness, evenness, distribution, the relationship between environmental characteristics to anuran assemblage, and species indicator. Ten permanent quadrats measuring 25 m x 25 m were installed in the restoration area. While 400 m transect line with an interval distance of 20 m were carried out in the adjacent forest. A total of 15 species of anuran belonging to six families was recorded in both habitats. Duttaphrynus melanostictus (56.0%) and Rhacophorus bipunctatus (43.7%) were the highest captured in the restoration site and forest respectively. The Shannon-Wiener Diversity Index, (H’) showed high species diversity in the forest (H’= 1.71). However, the species evenness in the forest is low (E= 0.42). Microhabitat structures showed a significant trend with the anuran species; horizontal position (F= 1.18, p< 0.05), vertical position (F= 1.45, p< 0.05), and substrate position (F= 1.15, p< 0.05). However, soil moisture and soil pH were insignificant (F= 0.1, p> 0.05). The vegetation percentage cover was statistically significant with the anuran abundance, (F= 1.56, p< 0.05). The macroclimate factors such as relative humidity (rs= -0.34, p< 0.05), wind speed (rs= 0.43, p< 0.05), and rainfall (rs= 0.07, p< 0.05) have a significant but weaker correlations with the species richness in both habitats. Correlation analysis for microclimatic factors (temperature, relative humidity) in the restoration showed temperature (rs= -0.65, p< 0.05) has a strong negative correlation to the abundance of D. melanostictus and relative humidity (rs= 0.51, p< 0.05) has a strong positive correlation to Polypedates leucomystax, whereas in the forest, relative humidity (rs= -0.93, p< 0.05) has a very strong negative correlation to Microhyla annectens. Duttaphrynus melanostictus and P. leucomystax in restoration area and R. bipunctatus in the adjacent forest were identified as best indicator species. Restoration area has great potential of harbouring more species diversity. Therefore, these findings provide an understanding of the habitat requirements needed by the anuran inhabiting a degraded forest.